THE EFFECT OF SCARCITY PROMOTIONS IN LIVE STREAMING E-COMMERCE ON PURCHASE INTENTION WITH THE MEDIATION ROLE OF EMOTIONAL EXPERIENCE ON GENERATION Z AND MILLENNIALS IN DKI JAKARTA - Pek Caih Sin; Agung Stefanus Kembau (Journal of Management Small and Medium Enterprises (SMEs), 2025)
The expansion of Indonesia’s digital economy has encouraged the adoption of live streaming as a marketing strategy, particularly within the e-commerce sector. This approach is efficient in capturing the attention of Generation Z and Millennials, who comprise the primary consumer base. This study examines the impact of scarcity-based promotions on purchase intention, with emotional experience serving as a mediating factor, focusing on Generation Z and Millennial consumers in DKI Jakarta. A quantitative methodology was employed, using a survey distributed via questionnaires to live streaming e-commerce users from both generations. The collected data were analyzed using SmartPLS version 4.1.1.2. Findings reveal that Limited Quantity Promotions (LQP) positively and significantly affect purchase intention, both directly and indirectly through emotional experience. In contrast, Limited Time Promotions (LTP) do not show a significant impact. LQP appears particularly effective among Generation Z and female consumers. Based on these results, it is recommended that e-commerce businesses prioritize implementing LQP strategies while ensuring LTP campaigns are applied consistently and effectively. Keywords: S-O-R; e-commerce; Live streaming E-commerce; Scarcity Promotions; Limited Time Promotions; Limited Quantity Promotions; Emotional Experience; Purchase Intention; Generation Z; Millennial Generation